Analisis Perkembangan Kognitif dan Fisik-Motorik Anak Usia Dini Melalui Proses Pembelajaran Direct Instruction: Analysis of Early Childhood Cognitive and Physical-Motor Development Through Direct Instruction Learning Processes - Depalina, Syamsiah; matondang, Devisaputri (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2022)
This research was conducted to analyze the cognitive and physical motor development of children through the direct instruction learning process. Direct Instruction is a learning process that is carried out directly which aims to achieve learning objectives. Direct Instruction can also improve children's cognitive and motor skills. This cognitive aspect is related to children's intelligence. Meanwhile, physical motor skills are related to the physical and mental development of children. This research is a qualitative research using Direct Instruction learning experiment. In this study, there are various research instruments, including experimental instruments, questionnaires, interview observations and tests. (Sugiyono, 2018). So, in this proposal, we will discuss how children's cognitive development and children's physical motor skills will develop, whether children's cognitive and physical motor skills will develop if there is a Direct Instruction learning experiment. The results of the research that can be obtained from the researcher are that the cognitive and physical motor skills of children can be improved from this Direct Instruction learning process. Not only that, Direct Instruction learning can also train children's mental and self-confidence.